The effect of a brief social intervention on the examination results of UK medical students: a cluster randomised controlled trial - Woolf, Katherine (BioMed Central, 2009)
BACKGROUND: Ethnic minority (EM) medical students and doctors underperform academically, but little evidence exists on how to ameliorate the problem. Psychologists Cohen et al. recently demonstrated that a written self-affirmation intervention substantially improved EM adolescents' school grades several months later. Cohen et al.'s methods were replicated in the different setting of UK undergraduate medical education. METHODS: All 348 Year 3 white (W) and EM students at one UK medical school were randomly allocated to an intervention condition (writing about one's own values) or a control condition (writing about another's values), via their tutor group. Students and assessors were blind to the existence of the study. Group comparisons on post-intervention written and OSCE (clinical) assessment scores adjusted for baseline written assessment scores were made using two-way analysis of covariance. All assessment scores were transformed to z-scores (mean = 0 standard deviation = 1) for ease of comparison. Comparisons between types of words used in essays were calculated using t-tests. The study was covered by University Ethics Committee guidelines. RESULTS: Groups were statistically identical at baseline on demographic and psychological factors, and analysis was by intention to treat [intervention group EM n = 95, W n = 79; control group EM n = 77; W n = 84]. As predicted, there was a significant ethnicity by intervention interaction [F(4,334) = 5.74; p = 0.017] on the written assessment. Unexpectedly, this was due to decreased scores in the W intervention group [mean difference = 0.283; (95% CI = 0.093 to 0.474] not improved EM intervention group scores [mean difference = -0.060 (95% CI = -0.268 to 0.148)]. On the OSCE, both W and EM intervention groups outperformed controls [mean difference = 0.261; (95%CI = -0.047 to -0.476; p = 0.013)]. The intervention group used more optimistic words (p < 0.001) and more "I" and "self" pronouns in their essays (p < 0.001), whereas the control group used more "other" pronouns (p < 0.001) and more negations (p < 0.001). DISCUSSION: Cohen et al.'s finding that a brief self-affirmation task narrowed the ethnic academic achievement gap was replicated on the written assessment but against expectations, this was due to reduced performance in the W group. On the OSCE, the intervention improved performance in both W and EM groups. In the intervention condition, participants tended to write about themselves and used more optimistic words than in the control group, indicating the task was completed as requested. The study shows that minimal interventions can have substantial educational outcomes several months later, which has implications for the multitude of seemingly trivial changes in teaching that are made on an everyday basis, whose consequences are never formally assessed.